Enhanced adsorption of crystal violet by synthesized and characterized chitin nano whiskers from shrimp shell. (December 2016) - Gopi, Sreerag; Pius, Anitha; Thomas, Sabu
Graphical abstract: Highlights: Native, treated chitin and chitin nanowhiskers were synthesized and characterized using FE-SEM, AFM and TEM. Prepared chitin nanowhiskers were used for crystal violet adsorption and the results were compared with other adsorbents. The adsorption capacity and removal efficiency were excellent for chitin nanowhiskers. Abstract: Chitin nanowhiskers (ChNW) were extracted from shrimp shell and subjected to alkali, bleaching and acid hydrolysis treatment. The Fourier transform infrared (FTIR) spectra confirmed the functional group moieties present at each stage of the purification process. The X-ray diffraction (XRD) analysis determined the crystallinity of the ChNW. The scanning electron microscopic (SEM), transmission electron microscopic (TEM) and atomic force microscopic (AFM) studies were carried out to examine and compare the morphology of the products at each stage of purification. The synthesized ChNW were used for the crystal violet adsorption studies. Along with ChNW, a series of adsorbent materials like chitin-Fe3 O4, cellulose, and cellulose − Fe3 O4 were used for comparing the results and for the better understanding of adsorption phenomena. The absorbance of the solution during a time interval was investigated using UV–vis spectrophotometry. The prepared ChNW showed higher removal efficiency (79.13%) and adsorption capacity (39.56 mg g −1 ) compared to other adsorbents. The results proved that ChNW can be a potential candidate for the removal of crystal violet from contaminated water.